Maximizing cancer prevention through genetic navigation for Lynch syndrome detection in women with newly diagnosed endometrial and nonserous/nonmucinous epithelial ovarian cancer. Issue 17 (13th May 2021) - Kim, Soyoun Rachel; Tone, Alicia; Kim, Raymond H.; Cesari, Matthew; Clarke, Blaise A.; Eiriksson, Lua; Hart, Tae L.; Aronson, Melyssa; Holter, Spring; Lytwyn, Alice; Maganti, Manjula; Oldfield, Leslie; et al.
Abstract : Background: Despite recommendations for reflex immunohistochemistry (IHC) for mismatch repair (MMR) proteins to identify Lynch syndrome (LS), the uptake of genetic assessment by those who meet referral criteria is low. The authors implemented a comprehensive genetic navigation program to increase the uptake of genetic testing for LS in patients with endometrial cancer (EC) or nonserous/nonmucinous ovarian cancer (OC). Methods: Participants with newly diagnosed EC or OC were prospectively recruited from 3 cancer centers in Ontario, Canada. Family history questionnaires were used to assess LS‐specific family history. Reflex IHC for MMR proteins was performed with the inclusion of clinical directives in pathology reports. A trained genetic navigator initiated a genetic referral on behalf of the treating physician and facilitated genetic referrals to the closest genetics center. Results: A total of 841 participants (642 with EC, 172 with OC, and 27 with synchronous EC/OC) consented to the study; 194 (23%) were MMR‐deficient by IHC. Overall, 170 women (20%) were eligible for a genetic assessment for LS: 35 on the basis of their family history alone, 24 on the basis of their family history and IHC, 82 on the basis of IHC alone, and 29 on the basis of clinical discretion. After adjustments for participants who died (n = 6), 149 of 164 patients (91%) completed a genetic assessment, and 111 were offered and completed genetic testing. Thirty‐four women (4.0% of the total cohort and 30.6% of those with genetic testing) were diagnosed with LS: 5 with mutL homolog 1 ( MLH1 ), 9 with mutS homolog 2 ( MSH2 ), 15 with mutS homolog 6 ( MSH6 ), and 5 with PMS2 . Conclusions: The introduction of a navigated genetic program resulted in a high rate of genetic assessment (>90%) in patients with gynecologic cancer at risk for LS. Abstract : A navigated genetic system significantly increases the uptake of genetic assessment for women with endometrial and nonserous/nonmucinous ovarian cancers at high risk of Lynch syndrome.